PERAN PRIVATE MILITARY COMPANY (PMC) DALAM KONFLIK KRISIS KEPRESIDENAN VENEZUELA 2018-2020 - Mulyadi, Ahmad; Aisha, Nina Widyaswasti; Prabowo, Ramiro (Universitas Prof. Dr. Moestopo (Beragama), 2024)
This research aims to analyze The Role of Private Military Companies (PMC) in Conflict Venezuelan Presidential Crisis 2018-2020. The research method used is a descriptive research method with a qualitative approach, where data collection is carried out through book sources, journal articles, essays, theses, and also internet sites. This research uses the theory of hard power diplomacy, where hard power diplomacy is a